2018
DOI: 10.1161/jaha.118.009565
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lymphangiogenesis on Cardiac Remodeling After Ischemia and Reperfusion Injury

Abstract: Background Lymphatic vessels interconnect with blood vessels to form an elaborate system that aids in the control of tissue pressure and edema formation. Although the lymphatic system has been known to exist in a heart, little is known about the role the cardiac lymphatic system plays in the development of heart failure. Methods and Results Mice (C57 BL /6J, male, 8 to 12 weeks of age) were subjected to either myocardial ischemia or myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 48 publications
1
89
0
2
Order By: Relevance
“…Cardiac lymphangiogenesis plays a central role in maintaining fluid homeostasis for healthy heart contraction [18]. Recent studies have suggested that lymphangiogenesis improves cardiac function and healing by draining accumulated fluids and maintaining the physiological interstitial fluid equilibrium [19,20,70]. These studies, together with our RNA sequencing data, suggested that VCFs have a favorable expression of genes related to the regulation of blood and/or lymph vessel formation.…”
Section: Plos Onementioning
confidence: 56%
See 3 more Smart Citations
“…Cardiac lymphangiogenesis plays a central role in maintaining fluid homeostasis for healthy heart contraction [18]. Recent studies have suggested that lymphangiogenesis improves cardiac function and healing by draining accumulated fluids and maintaining the physiological interstitial fluid equilibrium [19,20,70]. These studies, together with our RNA sequencing data, suggested that VCFs have a favorable expression of genes related to the regulation of blood and/or lymph vessel formation.…”
Section: Plos Onementioning
confidence: 56%
“…Additionally, numerous studies have reported that cardiac lymphatic vessels play a key role in maintaining fluid homeostasis, which is critical for healthy heart contraction [18]. Recently, targeting cardiac lymphatic vasculature is thought to provide a therapeutic benefit to heart function after myocardial infarction [19,20]. Thus, we hypothesized that VCFs might have the potential to improve cardiac function in heart failure by triggering angiogenesis and/or lymphangiogenesis.…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the detrimental relationship between lymphangiogenesis in cancer, an expanded lymphatic network during infection facilitates immune cell trafficking to infected tissues and helps mobilize the associated increase in interstitial fluid. In this way, lymphangiogenesis also contributes to tissue regeneration, leading to improved outcomes following wound and ischemic injury events …”
Section: Lymphangiogenesis Is a Double‐edged Sword In Diseasementioning
confidence: 99%